YOUTH IN SPORTS CLUBS: ON THE ROLE OF SPORTS CLUBS IN THE SOCIAL INTEGRATION IN HUNGARY - Török, Emőke (Society Register, 2018)
It is a widely accepted view that the participation of young generations in organized sports activities has positive impacts both for the individual and the society. However, these positive impacts often does not reach those groups of the society, which would need the most these impacts for improving their chances regarding social participation and thus promoting integration of the society. The paper presents the results of a survey among young athletes inHungary, showing that the perception of the athletes in the sports clubs is very positive regarding the impacts of sports on their lives, but that young people from low-income and low-education families have very limited access to the sports clubs and so to the positive impacts of sports.